The roles of a pediatric pulmonologist during the COVID‐19 pandemic. Issue 10 (17th August 2020) - Kazachkov, Mikhail; Noah, Terry L.; Murphy, Thomas M.
Abstract: Pediatric pulmonologists have been involved in the care of adult COVID‐19 patients in a variety of ways, particularly in areas with a high concentration of cases. This invited commentary is a series of questions to Dr Mikhail Kazachkov, a pediatric pulmonologist at New York University, about his experiences to date in a major COVID‐19 "hotspot" and his thoughts about how other pediatric pulmonologists facing this situation can best support their colleagues.